USE OF REGENERATIVE THERAPIES (PRP OR STEM CELLS) IN THE ORTHOPEDIC POSTOPERATIVE PERIOD OF DOGS WITH HIP DYSPLASIA (International Seven Journal of Multidisciplinary, 2025)
Objective: To evaluate the main effects of regenerative therapies, such as mesenchymal stem cells (MSC) and platelet-rich plasma (PRP), in the postoperative treatment of dogs with hip dysplasia (HD), and correlate them with clinical and laboratory outcomes. Hip dysplasia is a common orthopedic disease in dogs, particularly in large breed dogs, and often leads to degenerative joint diseases such as osteoarthritis. The combination of MSC and PRP has shown promising effects on cartilage regeneration and pain relief, but the effectiveness of these treatments still depends on factors such as the severity of the disease and the stage of progression. This literature review analyzed national and international studies on the use of these regenerative therapies in the treatment of HD, highlighting clinical protocols, therapeutic effects, and limitations observed in different stages of the disease. The results show that, although these therapies present significant potential, standardization of protocols and conducting long-term studies are essential for confirming their effectiveness and safety.